ROCK inhibitors upregulate the neuroprotective Parkin-mediated mitophagy pathway - Natalia Moskal; Victoria Riccio; Mikhail Bashkurov; Rediet Taddese; Alessandro Datti; Peter N. Lewis; G. Angus McQuibban (2020)
Abstract The accumulation of damaged mitochondria causes the death of dopaminergic neurons. The Parkin-mediated mitophagy pathway functions to remove these mitochondria from cells. Targeting this pathway represents a therapeutic strategy for several neurodegenerative diseases, most notably Parkinson’s disease. We describe a discovery pipeline to identify small molecules that increase Parkin recruitment to damaged mitochondria and ensuing mitophagy. We show that ROCK inhibitors promote the activity of this pathway by increasing the recruitment of HK2, a positive regulator of Parkin, to mitochondria. This leads to the increased targeting of mitochondria to lysosomes and removal of damaged mitochondria from cells. Furthermore, ROCK inhibitors demonstrate neuroprotective effects in flies subjected to paraquat, a parkinsonian toxin that induces mitochondrial damage. Importantly, parkin and rok are required for these effects, revealing a signaling axis which controls Parkin-mediated mitophagy that may be exploited for the development of Parkinson’s disease therapeutics.